Accountability regarding the conflict in Gaza and southern Israel : written statement to the Human Rights Council, thirteenth session, March 2010 - Amnesty International (2010)
This written statement by Amnesty International to the Human Rights Council (HRC), submitted on 15 February 2010 ahead of the 13th HRC session of 1-26 March 2010, gives an account and an assessment of Israeli and Palestinian investigations to date into serious violations of international law alleged to have taken place in the context of 22 days of hostilities in Gaza and southern Israel between 27 December 2008 and 18 January 2009. It concludes that none of the parties to the conflict conducted investigations "that are independent, credible and in conformity with international standards" - the criteria set out for them by the UN General Assembly.